2002
DOI: 10.1056/nejmoa013168
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Resynchronization in Chronic Heart Failure

Abstract: Cardiac resynchronization results in significant clinical improvement in patients who have moderate-to-severe heart failure and an intraventricular conduction delay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

83
2,321
14
78

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 4,325 publications
(2,564 citation statements)
references
References 35 publications
83
2,321
14
78
Order By: Relevance
“…The lack of statistically significant improvement in VO 2 max was similar to the results of some previously reported CRT studies19, 20 although CRT has also been shown to improve VO 2 max 2. In addition, there was a significant reduction in the plasma concentrations of N‐terminal proBNP, a similar finding to the CARE‐HF trial 2. In this regard, a post hoc analysis of the MADIT‐CRT trial21 found that reduction in BNP following CRT was associated with significant decrease in hospitalized heart failure and mortality.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The lack of statistically significant improvement in VO 2 max was similar to the results of some previously reported CRT studies19, 20 although CRT has also been shown to improve VO 2 max 2. In addition, there was a significant reduction in the plasma concentrations of N‐terminal proBNP, a similar finding to the CARE‐HF trial 2. In this regard, a post hoc analysis of the MADIT‐CRT trial21 found that reduction in BNP following CRT was associated with significant decrease in hospitalized heart failure and mortality.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, we have a cohort in whom there was effective mechanical cardiac resynchronization; otherwise, it would have been futile for us to proceed with the pursuit of understanding of any further mechanistic effect of CRT. The lack of statistically significant improvement in VO 2 max was similar to the results of some previously reported CRT studies19, 20 although CRT has also been shown to improve VO 2 max 2. In addition, there was a significant reduction in the plasma concentrations of N‐terminal proBNP, a similar finding to the CARE‐HF trial 2.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Cardiac resynchronization therapy (CRT) is recommended by current guidelines for the treatment of patients with symptomatic heart failure (HF), impaired left ventricular (LV) systolic function, and an electrocardiogram (ECG) which displays evidence of electrical dyssynchrony,1, 2 with established effects on morbidity and mortality 3, 4. However, in spite of the overall beneficial effects of CRT, no early clinical improvement is observed in approximately 30% of CRT recipients 3, 5…”
Section: Introductionmentioning
confidence: 99%